Unravelling heart failure cellular signalling heterogeneity with spatial transcriptomics - Tual-Chalot, Simon; Stellos, Konstantinos (European heart journal, 2025)
This editorial refers to ‘Spatial transcriptional landscape of human heart failure’, by S.E. Lee et al., https://doi.org/10.1093/eurheartj/ehaf272.Heart failure (HF) is characterized by the inability of the heart to pump blood at a rate that covers the metabolic demands of the body. HF results from structural or functional heart abnormalities and often arises from conditions such as chronic coronary insufficiency, myocardial infarction, arterial hypertension, diabetes mellitus, amyloidosis, infectious diseases, chemotherapy- and radiotherapy-induced cardiomyopathy, congenital heart defects, genetic disorders, or ageing.1,2 Over 64 million people worldwide are living with HF, with an increasing prevalence due to population ageing and improved survival after an acute heart attack.1 Advances in treatment have improved outcomes for many patients, but HF remains a condition with significant long-term mortality. The lifetime risk of developing HF at age 50 ranges from 22.5% for women to 25.5% for men,3 and its prognosis remains poor, with a 5-year survival rate below 50%.1 Currently, there is no definitive cure for HF, and treatment focuses on managing symptoms, improving quality of life, and slowing disease progression.
Online veröffentlicht: 30. Mai 2025
Gesehen am 26.08.2025